POLITICAL ECONOMICS MEDIA: AT THE BANTEN SELECTION OF 2011 BY RADAR BANTEN AND BARAYA TV - Priatna, Ahmad Nashrudin (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2017)
The mass media, whether print or broadcast (TV and Radio) plays a significant role in disseminating important messages to the public / society. Karl Marx said "that the media referred to as the class that set, in the system of modern capitalism. So therefore the media in the present era, into a commodity economy and politics, because of its function and because ownership massive by individuals (owners of capital). That allows, position the media and not only to function as a disseminator of information, but because of the ownership of such individuals, are very likely to be a tool for "political dealings", rather than as a function of social control. in the practice of political communication, media becomes a medium that is not inevitable in conveying messages politics, especially during the campaign, the elections political leadership, good legislative elections, presidential elections, and the elections. Radar Banten and Baraya TV is a media agency which is recognized as a great and influential in Banten province, which is a member of the Jawa Pos ( Java Post News Network) beperan menyerbarluaskan major messages of the prospective head region in the activities of the campaign. The phenomenon of political economic practices, be a gamble for the function and positioning to the two media institutions. Is capable of functioning media (read: news) or more tend to promote the business side, perhaps, their political position.?Keywords: media, political communication, the Regional Head Election (Election) Banten, The political economy of the media